Integrated Marketing Management Strategies in the Digital Age: Comprehensive Analysis and Case Studies - Musaiyadi, Musaiyadi; Salim, Helmi Agus; Gerhani, Febrina (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This article examines the development and implementation of integrated marketing management strategies in the context of the digital age. Through a comprehensive analysis of current literature and case studies from various industries, this research aims to provide an in-depth understanding of how companies can optimize their marketing strategies amid changes in the digital landscape. The methodology used includes a systematic literature review, secondary data analysis, and multiple case studies. The results indicate that the integration of digital technology, personalization of customer experiences, and the utilization of big data are key to the success of contemporary marketing strategies. In conclusion, companies need to adopt a more adaptive and technology-oriented approach to their marketing management to remain competitive in the digital age